Systematic Construction of Criminal Policy in the Defense Industry Law Partially Amended by the Job Creation Law - Akhyar, Wira Iqomudin; Deksino, G. Royke; Jupriyanto, Jupriyanto (Fakultas Hukum Universitas Islam Jakarta, 2024)
Criminal law issues strengthen the commonly used administrative law policies. However, the systematic construction of criminal provisions in a law has the potential to